ENRICHMENT OF REE ION-ADSORPTION AT WEATHERED GRANITE CRUSTS RELATED TO REE MINERALIZATION ON GRANITIC ROCKS IN BANGKA ISLAND - Rasma, Periska
Bangka Island consists of granite plutons which mineralized by REE-bearing minerals such as monazite, xenotime, apatite, allanite and titanite. Regarding the weathering process, it allows REE ion-adsorption deposits that absorb REE ions within clay minerals. REE ion-adsorption on weathered granite contains lower radioactive elements with easier extraction processes. This study aims to determine the mineralogical and geochemical REE at weathered granite in Bangka Island. Samples were taken from IAD-01 and IAD-10. Petrography of granite was observed using refraction microscope, and the presence of REE-bearing minerals and clay minerals in granite and weathered granite were analyzed using X-Ray Diffraction. The major elements, trace elements and REE were analyzed by X-Ray Fluoresence and Induced Coupled Plasma-Mass spectrometry. Based on mineralogical data, granite rock thought to mineralized by REE, and the weathered granite contains kaolinite and halloysite. The highest REE content from weathered zone at horizon B of the IAD-01 and horizon A of IAD-10. Light REE enrichment over heavy REE comes from Ce, which is thought to be absorbed by clay, and re-mineralized to fluocerite. REE was normalized to UCC and showed a positive Ce anomaly indicating the weathered granite zones are REE leach zone, not an accumulation zone. In addition, TREE content of the samples is not yet economical, because it is less than 500 ppm.